Associations Between Objective Sleep Behaviors and Blood Glucose Variability in Young Children With Type 1 Diabetes. Issue 2 (15th June 2020) - Monzon, Alexandra D; Marker, Arwen M; Noser, Amy E; Clements, Mark A; Patton, Susana R
Abstract: Background: Young children with Type 1 diabetes (T1D) are at risk for extreme blood glucose variability, a risk factor for suboptimal glycated hemoglobin A1c (HbA1c) and long-term health complications. We know that a reciprocal relationship exists between sleep and glycemic outcomes in older youth with T1D; however, little research has examined objective sleep in young children (<7 years) with T1D. Purpose: This study examines bidirectional associations between sleep behaviors and glycemic variability in young children with T1D. Methods: Thirty-nine young children with T1D ( M age 4.33 ± 1.46 years; M HbA1c 8.10 ± 1.06%) provided accelerometry data to objectively measure sleep onset latency, number of nighttime awakenings, and total sleep time. We also assessed HbA1c, average blood glucose, and glycemic variability (i.e., standard deviation of blood glucose from device downloads). We evaluated bidirectional relationships using multilevel modeling in SAS, with weekday/weekend as a Level 2 moderator. Results: Children averaged 8.5 ± 1.44 hr of sleep per night, but only 12.8% met current sleep recommendations. Children experienced more nighttime awakenings, higher blood glucose, and more glycemic variability on weekends. Sleep onset latency and nighttime awakenings predicted greater glycemic variability on weekends, and weekend glycemic variability predicted increased nighttime awakenings. Conclusions: Most young children with T1D did not meet sleep recommendations. Young children experienced more nighttime awakenings, higher blood glucose, and increased glycemic variability on weekends only, when routines may be less predictable. Findings suggest that one way families of young children with T1D may be able to decrease glycemic variability is to keep consistent routines on weekdays and weekends. Abstract : Young children with type 1 diabetes may experience more sleep disturbances, higher blood glucose levels, and increased glycemic variability on weekends.